Accommodating children with mobility impairments in ordinary primary schools : perceptions of school principals in Johannesburg East on barriers and possible solutions - Hunt, Paulani (Stellenbosch : Stellenbosch University, 2021)
Thesis (MHumanRehabSt)--Stellenbosch University, 2022.